(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Medical students experience the transition between preclinical and clinical training as a stressful period, as preparedness for practice as new doctors is associated with patient safety issues. Objective: To explore medical students/graduates’ perception regarding methods of assessments, feedback, support and new responsibilities. Methods: A cross-sectional analysis was carried out online using google form sent to all medical colleges of Iraq during March-May 2023 on stagiaire and first year graduates to inquire about their opinions regarding their clinical training. Results: From 250 responses received from different universities, 37.3% of students found the educational sessions are most useful for training, 14.1% found they are not useful and 5.6% don’t attend the educational sessions. Majority of Al-Nahrain students have adapted new responsibilities (60%), most of them have chosen group members as their main supporters (46%) and most of them have suggested skill labs as a method for improvement in future sessions. Conclusion: The majority of the students found that the educational sessions and skill lab are the most useful tools for preparedness and clinical training. Keywords: Clinical training, medical education, stagiaire, skill lab Citation: Mohammed LK. Perception of stagiaires and freshly graduates regarding clinical training of the final year medical college. Iraqi JMS. 2024; 22(2): 203-211. doi: 10.22578/IJMS.22.2.3